Learning Management in order to Improve the Quality of Madrasah Aliyah Graduates - Evi Erfiyana; Opan Arifudin; Annisa Mayasari; Silvi Herawati; Atik Rosanti; Rachmad Agung Prayogi (Journal of General Education and Humanities, 2026)
The urgent need to improve the quality of learning in order to produce high-quality graduates has become a major challenge in the Management of education at Madrasah Aliyah. The problems identified include a lack of innovation in learning strategies and the suboptimal Management of the learning process in response to contemporary educational demands. This study aims to describe and analyze the implementation of learning management at Madrasah Aliyah in an effort to enhance the quality of graduates. This research employed a descriptive qualitative approach, focusing on the process of learning management, strategies for developing students’ competencies, and the supporting and inhibiting factors in its implementation. Data were collected through observations, in-depth interviews, and documentation studies involving the head of the madrasah, teachers, and students. The findings indicate that the implementation of effective, well-planned, and innovative learning management can enhance students’ learning motivation and graduate competencies. However, several challenges remain, particularly related to limited resources and insufficient teacher training. These findings are expected to provide input and recommendations for optimizing learning management to further improve the quality of Madrasah Aliyah graduates.